Communication Strategy of Culture Service to Promote Heritage of Historical Buildings from Medan City - Elok Perwirawati (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This study aims to determine how the communication strategy of the cultural department of Medan city to promote the heritage buildings. The benefits of this study are to increase the author's experience through the research conducted and to provide information to those who pay attention to cultural heritage and handling. This study used a qualitative descriptive method which authors collected data via interviews and observation, literature study and documentation. The study conducted at the Department of Culture in Medan, and the primary data collecting by observation, interviews and the secondary data obtained within the study of literature, books and also internet sites that have relevance to the object of this study. The results showed that the communication strategy of Cultural Department in Medan City to promote the heritage of historical buildings is effective. Cultural heritage promotion activities were taking place from the determination of the target audience, preparation of an appropriate message, delivery methods, and the selection of suitable media, so the message conveys appropriately to the audience targeted.